The role of coopetition, knowledge management and trust towards innovative work behavior - Matondang, Rizki; Fahmy, Rahmi; Rahman, Hafiz (Institute of Computer Science (IOCS), 2024)
This research aims to analyze the influence of coopetition and knowledge management on innovative work behavior with trust as a mediating variable. Research data processing was carried out using the SEM (Structural Equation Modeling) method, with the type of Structure Equation Modeling (SEM) used, namely Smart PLS. The research results show that knowledge management, trust have a positive and significant influence on innovative work behavior, and trust can have a mediating effect on the knowledge management variable on innovative work behavior. However, the coopetition variable has not been able to influence innovative work behavior and trust has not been able to act as an intermediary between the coopetition variable and innovative work behavior